Publicly tasting cultivated meat and socially constructing perceived value politics and identity - Suzannah Gerber; Hyeryeon Bae; Isabella Ramirez; Sean B. Cash (npj Science of Food)
Abstract Cultivated meat (CM), derived from animal cells without traditional animal agriculture, offers potential to address vulnerabilities and reduce negative impacts of meat production. However, CM faces consumer skepticism, regulatory hurdles, and bans in some U.S. and European states. Key gaps in understanding include acceptance, sensory evaluation, and political alignment with existing research relying primarily on hypothetical, experiment-based evaluations. This study is the first to observe consumer acceptance in a public tasting of CM. We conducted an ethnographic analysis combining semi-structured interviews, field observations, and secondary data from media and social media including additional interviews. Using Grounded Theory, we identified themes—American identity, verisimilitude, and the role of government—that inform pathways for CM acceptance. Results reveal the importance of aligning CM with ethical priorities while meeting sensory and transparency expectations to build consumer trust. Widespread adoption may require further innovation, evidence-based communication, and consumer inclusion for CM to be seen as a valuable alternative to conventional meat.